Model Tata Kelola Badan Usaha Milik Desa (BUMDes) di Desa Sigaluh, Kecamatan Sigaluh, Kabupaten Banjarnegara - Arofah, Triani; Ramadhanti, Wita; Rusmana, Oman (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
BUMDes was established to improve the economic resilience of the village. The objective of establishing BUMDes will not be achieved unless BUMDes governance runs effectively in accordance with BUMDes governance principles. Sigaluh Village is one of the villages in Sigaluh Sub-district, Banjarnegara Regency that has a BUMDes with an active status but has not been operating properly. The manager's lack of knowledge and understanding of BUMDes good governance is one of the causes of BUMDes activities not being carried out. This charity activity aims to help find solutions so that BUMDes can be managed effectively. Strengthening governance principles through collaborative, participatory, emancipative, transparent, accountable and sustainable actions is the model developed in this activity.